Hubungan Antara Fear of Missing Out (Fomo) dengan Efikasi Diri Mahasiswa yang Sedang Mengerjakan Skripsi Pasca Pandemi Covid-19 - Dwiyanti, Nurma; Nuryanti, Sofia (Jurnal Ilmiah Psikologi (JIPSI), 2022)
The purpose of this research is to find out the relevance between Fear of Missing Out (FoMO) and the self-efficacy of students who are working on post-Covid-19 thesis work. The urgency of this research lies in the importance of a person's self-efficacy ability in facing various kinds of pressures and obstacles to be able to overcome them, so as to achieve goals. This study uses a quantitative method with the criteria to be used, namely final year students working on a thesis, experiencing a lecture transition online, then currently undergoing lecture activities which include apprenticeship exams, thesis exams, tutoring and so on through face-to-face, aged 20 - 26 years old, active social media user. Determination of respondents using non-probability sampling techniques and accidental sampling techniques used in this study to obtain 142 respondents. The instrument used is the Indonesian version of FoMOS taken from Triani (2017), which has trans adapted and modified from Przybylski, et al (2013) and Reagle (2017) and the self-efficacy scale taken from Adelina (2018) which is a trans adaptation and modification of Sherer et al. (1982). Hypothesis testing was carried out using the Product Moment Pearson correlation technique using SPSS for Windows version 22. The results showed that there was a significant relationship in the direction of a negative correlation between FoMO and the self-efficacy of students working on post-Covid-19 thesis, where the two variables were at medium correlation level.